2011
DOI: 10.1177/1040638711408280
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic findings in a dog with a retrobulbar meningioma

Abstract: Abstract. An 11-year-old Fox Terrier dog was evaluated for a 10-month history of progressive exophthalmia and visual deficits in the right eye. Ophthalmologic examination revealed severe corneal fibrosis and pigmentation, which obscured examination of the anterior chamber of the right eye. There was decreased retropulsion of the right eye. Neurological examination revealed an absent menace response bilaterally. Pupillary light reflex was normal in the left eye. Due to the corneal pathology, pupillary light ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Optic nerve atrophy and degeneration and retrograde retinal atrophy with loss of ganglion cells are frequent secondary findings. Larger masses may cause bone remodeling . Orbital meningiomas are immunoreactive for vimentin and NSE.…”
Section: Orbital Neoplasiamentioning
confidence: 99%
See 2 more Smart Citations
“…Optic nerve atrophy and degeneration and retrograde retinal atrophy with loss of ganglion cells are frequent secondary findings. Larger masses may cause bone remodeling . Orbital meningiomas are immunoreactive for vimentin and NSE.…”
Section: Orbital Neoplasiamentioning
confidence: 99%
“…Some are immunopositive for S100, e‐cadherin, and GFAP. The neoplastic cells are immunonegative for cytokeratin . The prognosis for life is fair to guarded, as local recurrence may occur.…”
Section: Orbital Neoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…MRI findings of CNS GCTs in domestic animals are scarce (Higgins et al 2001, Liu et al 2004, Sharkey et al 2004, Klopp & Ridway 2009, Rao et al 2010, Regan et al 2011, Mishra et al 2012, Anwer et al 2013. Based on these reports, pre-contrast T1W hyperintensity seems to be a consistently striking feature of canine CNS GCT.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, domestic animals seem to be rarely affected. To date, intracranial GCTs have been described in 16 dogs (Parker et al 1978, Patnaik 1993, Barnhart et al 2001, Higgins et al 2001, Liu et al 2004, Sharkey et al 2004, Klopp & Ridway 2009, Regan et al 2011, Mishra et al 2012, Anwer et al 2013) and one cat (Mandara et al 2006), whereas spinal GCTs have been reported only in two dogs (Montoliu et al 2006, Rao et al 2010.…”
Section: Introductionmentioning
confidence: 99%